PERANAN BELAJAR JARAK JAUH DALAM PEMERATAAN AKSES PENDIDIKAN DI INDONESIA - Kirwati, Sri (Jurnal Ilmu Budaya, 2008)
This writing deals with distance learning in which it has important role in assisting students who live far away from the educational institution, due tue their inability to get from their job. In this case, distance learning gives a way out for those who are eager to increase their intellectual capability. Since distance learning doesn't provide a condition in which teacher and students are located in one classroom, so, the student self motivation is highly expected to study independently, to work hard and to have discipline.